NILAI EKONOMI PUSAT LATIHAN GAJAH DI TAMAN NASIONAL WAY KAMBAS - Ikhsan Pandu Wibowo; Susni Herwanti; Indra Gumay Febryano; Gunardi Djoko Winarno (Jurnal Hutan Tropis, 2019)
The Elephant Training Center is a tourist attraction frequented by people in Lampung Province.  This study aims to analyze the travel cost of each zone and determine economic value total Elephant Training Center.  Data collection method is by direct interview using questionnaires and sampling using purposive sampling technique.  Calculation of economic value is determined based on the (Travel Cost Method).  The results revealed the travel costs in East Lampung Regency were Rp 119,558, Metro City Rp 207,638, Bandar Lampung City Rp 178,244, Central Lampung District Rp 169,320, North Lampung District Rp 180,255, South Lampung District Rp 188,759, Pringsewu District Rp 227,428, Tanggamus District Rp. 224,004, Way Kanan Regency Rp 232,003, District Tulang Bawang 303,001, South Sumatera Province/Oku South Rp 215,751, South Sumatera Province/Pali Rp 215,101 and Tangerang City Rp 359,010.  Meanwhile, the total travel cost of visitor was Rp 15.818.008/times of visit, the average cost of visitor was Rp 158.180/person/times of visit. The economic value of tourism services was Rp 5.429.555.090/year.  Increasing promotion and improving facilities and facilities needs to be done by the management so that the Elephant Training Center becomes a tourist attraction in East Lampung Regency.